anonymous
  • anonymous
solve for the two power series solution of the given differential equation: (x-1)y"-xy'+y=0 ; y(0)=-2, y'(0)=6
Mathematics
jamiebookeater
  • jamiebookeater
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
for analytic \(y\) we have $$y=\sum_{n=0}^\infty a_n x^n\\y'=\sum_{n=0}^\infty na_nx^{n-1}=\sum_{n=0}^\infty (n+1)a_{n+1}x^n\\y''=\sum_{n=0}^\infty n(n+1)a_{n+1}x^{n-1}=\sum_{n=0}^\infty (n+1)(n+2)a_{n+2} x^n$$and $$xy'=x\sum_{n=0}^\infty (n+1)a_{n+1}x^n=\sum_{n=0}^\infty (n+1)a_{n+1}x^{n+1}=\sum_{n=0}^\infty na_nx^n\\xy''=x\sum_{n=0}^\infty (n+1)(n+2)a_{n+2} x^n=\sum_{n=0}^\infty (n+1)(n+2)a_{n+2}x^{n+1}\\\quad\quad=\sum_{n=0}^\infty n(n+1)a_{n+1} x^n$$
anonymous
  • anonymous
so $$(x-1)y''-xy'+y=0\\\sum_{n=0}^\infty (n(n+1)a_{n+1}-(n+1)(n+2)a_{n+2}-na_n+a_n)=0\\n(n+1)a_{n+1}-(n+1)(n+2)a_{n+2}+(1-n)a_n=0\\a_{n+2}=\frac{1-n}{n(n+1)}a_n+\frac{n}{n+2}a_{n+1}$$
anonymous
  • anonymous
now consider $$y(0)=\sum_{n=0}^\infty a_n (0)^n=a_0\\y'(0)=\sum_{n=0}^\infty (n+1)a_{n+1}(0)^n=(0+1)a_{0+1}=a_1$$

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
so \(a_0=-2,a_1=6\) now evaluate them manually according to the recursion to try and find a pattern
anonymous
  • anonymous
oops, the recurrence should read: $$a_{n+2}=\frac{1-n}{(n+1)(n+2)}a_n+\frac{n}{n+2}a_{n+1}$$
anonymous
  • anonymous
so what's the final value for C_1,C_2,C_3,C_4 and so on..?
anonymous
  • anonymous
anyways $$\begin{array}{c|c|c}n&a_n\\\hline 0&-2\\1&6\\2&-1\\3&-\frac13\\4&-\frac1{12}\\5&\dots \end{array}$$
jtvatsim
  • jtvatsim
Oooh... this actually appears to have a very elegant final solution. :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.